St. Gregory Palamas - Walls, R. C. (Scottish journal of theology, 1968)
Six centuries ago, in 1368, a man who had been dead only nine years was canonised by the orthodox church and raised to the dignity of Athanasius, the Cappadocian Fathers, and of Cyril as a defender of orthodoxy. The sexcentenary of his death, 1959, saw the publication of three volumes—the first being one of the ‘Mâitres Spirituels’ series, the second an introduction to the study of St. Gregory, and the third and most important a critical edition of St. Gregory's major work: Treatise in defence of the Holy Solitaries. All three were the work of Jean Meyendorf who can rightly claim to have been the first scholar to have offered a full-dress sympathetic study to the west of a neglected and much misunderstood theologian. Unfortunately Meyendorf's work is spoilt by his inability to understand the reformed tradition. Nevertheless he has countered or at least challenged a settled assumption of western theology that the great christological debates saw the end of any lively thinking and dogmatic development in the Eastern Church. Harnack in his History of Dogma Vol. IV was only repeating what was already a long received opinion when he said that from the codification of dogma by John of Damascus those dogmas ‘had become a sacred inheritance from the classic antiquity of the Church but they had as it were fallen to the ground. The worship of images, mysticism and scholasticism ruled the Church’ (p. 352).But even Harnack gives at least a passing nod to St. Gregory when he admits that ‘no doubt another rather important dispute agitated the Church in the fourteenth century–the Hesychastic controversy–but’, he adds, ‘dogma, and to some extent the Church, remained ultimately unaffected’ (p.353).